(untitled) (Research, Society and Development, 2022)
Psychotropic drugs are medications that by acting mainly on the central nervous system, temporarily alter mood, behavior and consciousness, which are factors that corroborate to their non-medical use, especially within universities. The aim of this review was to analyze the prevalence of abusive consumption by students, besides discussing possible reasons and negative consequences. The bibliographic survey was carried out using the platforms PubMed and SciELO, from which 25 articles were selected for the review after using the descriptors “psychotropic drugs AND students”, “anxiolytics AND students” and “anxiety AND depression AND students” and applying the inclusion and exclusion criteria, from march to april of 2021. Through the analysis of the articles, it was seen that the high prevalence of non-medical consumption among university students is mainly marked by the use of central nervous system depressants, with recreational use, self-medication and improvement in academic performance being the aims listed. The relevance of the study was demonstrated by exposing possible health consequences of abusive use, in addition to identifying the predominance of consumption by females and the influence of the study load as the main reason for starting the non-medical use. In conclusion, it is important to raise awareness among students about the inappropriate consumption of prescribed medications, making clear the possible health impacts they may cause and the importance of dealing with stress in a healthy way.